Modeling the Optical System of NASA’s EXCLAIM Mission - Siebert, Gage L (Proceedings of the Wisconsin Space Conference, 2022)
NASA's EXperiment for Cryogenic Large-Aperture Intensity Mapping (EXCLAIM), is a balloon-borne instrument that is designed to perform intensity mapping of CO and CII at redshifts as high as z=3.5. It will map galaxy and star formation history over cosmological time. EXCLAIM will also demonstrate novel integrated silicon spectrometers using microwave kinetic inductance detectors (MKIDs) that could be an enabling technology for the Origins Space Telescope or other future mid- to far-infrared space telescopes. Here we present progress toward a full electromagnetic simulation of EXCLAIM's optical system at its operational frequencies. The goal of these simulations is to verify the design of the optical system meets mission requirements. When combined with measurements of the instrument, the simulation will also verify that our understanding of the optical system is complete. This work is being done in preparation for the first flight in mid 2022.